2021
DOI: 10.1177/10436596211035176
|View full text |Cite
|
Sign up to set email alerts
|

The Adherence to Healthy Lifestyle Among Arab Patients With Cardiovascular Disease: Mixed-Method Review

Abstract: Introduction Cardiovascular disease (CVD) accounts for 25% to 45% of deaths among Arab people. The purpose of this review was to investigate the level, predictors, motivators, and barriers to adherence to lifestyle recommendations among Arab patients with CVD. Method A systematic search of the literature was conducted and reported using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. MEDLINE, EMCARE, CINAHL, Scopus, and the Cochrane Central Register of Controlled Trials were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…According to research, women have lower socioeconomic status than men in general, which is related to gender inequality and may have a negative impact on health outcomes [ 34 ]. Furthermore, according to a recent literature review, women in the Middle East have lower physical activity time due to their busy schedules and home responsibilities, such as caring for extended family members and grandchildren [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to research, women have lower socioeconomic status than men in general, which is related to gender inequality and may have a negative impact on health outcomes [ 34 ]. Furthermore, according to a recent literature review, women in the Middle East have lower physical activity time due to their busy schedules and home responsibilities, such as caring for extended family members and grandchildren [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Authors found that medication adherence was 61% among chronic disease African Americans and 69% among Latinos (Simoni et al, 2012). Addressing disparities in medication adherence for CVD requires a collaborative health care approach that implements interventions designed to address culturally specific roots of nonadherence that may aid in patient adherence behavior (Alomari et al, 2022). Low medication adherence rates among Arab populations may be due to specific cultural and personal beliefs, such as the necessity of medication and attitudes toward taking daily medications, when compared with other ethnic groups.…”
Section: Discussionmentioning
confidence: 99%
“…Arabs’ reactions to medical problems and procedures are influenced by a variety of ever-changing local circumstances and social forces (Al-Ganmi et al, 2020). To overcome some of these medication adherence barriers, multifaceted interventions such as open communication with health care professionals must be implemented (Alomari et al, 2022). Health care professionals must ensure that they understand medication regimens, that dosage medication boxes are used, that smartphone apps that set medication reminders are used, and that partnerships between pharmacists and other health care professionals are strengthened.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By incorporating recent findings into ongoing research and practice to promote a healthy lifestyle, we could increase the prognosis for patients with cardiovascular disease (CVD). [10] Study done by bayad in February 2021on Iraqi Sample According to the study, Kurdish consumers place a high value on the freshness of food products and their organic status. They also worry about their eating habits and the accompanying health benefits.…”
Section: Introductionmentioning
confidence: 99%